Flexural Behavior of Steel Beam Strengthening by Prestressing Strands - Mohammed M. Rasheed, Dr.; Ali F. Atshan, Mr.; Kamal Sh. Mahmoud, Mr. (International Journal of Engineering and Technology, 2018)
Seven simply supported steel beams were tested to explain the effect of strengthening by external prestressing strands. All of the beams have the same steel section, clear span length and the strengthening samples which implemented by two external prestressing strands. The tested beams are divided into two categories according to existing of external prestressing strands, the first category consists of one steel beam as a reference, while, the second group deals with steel beams strengthening by external prestressing strands and consists of six steel beams divided according to the eccentricity location of prestressing strand with jacking stress (815 MPa). From experimental results, it was found that the moment curvature curves behavior for the tested beams are stiffer and with less ductility than the reference beams and the ultimate moment capacity is increased with increasing the eccentricity location. While, the maximum radius of curvature at bottom flange decreases with increasing the eccentricity location as compare with the reference beam.Â Â Â